The hepatitis C virus care cascade in the New York City jail system during the direct acting antiviral treatment era, 2014–2017. (October 2020) - Chan, Justin; Kaba, Fatos; Schwartz, Jessie; Bocour, Angelica; Akiyama, Matthew J; Rosner, Zachary; Winters, Ann; Yang, Patricia; MacDonald, Ross
Abstract: Background: High patient turnover presents challenges and opportunity to provide hepatitis C virus (HCV) care in US jails (remand facilities). This study describes the HCV care cascade in the New York City (NYC) jail system during the direct-acting antiviral (DAA) treatment era. Methods: Patients admitted to the NYC jail system from January 2014 through December 2017 were included in this retrospective cohort analysis. We describe rates of screening, diagnosis, linkage to jail-based care, and treatment among the overall cohort, and among subgroups with long jail stays (≥120 days) or frequent stays (≥10 admissions). The study protocol was approved by a third-party institutional review board (BRANY, Lake Success, NY). Findings: Among the 121, 371 patients in our analysis, HCV screening was performed in 40, 219 (33%), 4665 (12%) of whom were viremic, 1813 (39%) seen by an HCV clinician in jail, and 248 (5% of viremic patients) started on treatment in jail. Having a long stay (adjusted risk ratio [aRR] 8·11, 95% confidence interval [CI] 6·98, 9·42) or frequent stays (aRR 1·51, 95% CI 1·04, 2·18) were significantly associated with being seen by an HCV clinician. Patients with long stays had a higher rate of treatment (14% of viremic patients). Sustained virologic response at 12 weeks was achieved in 147/164 (90%) of patients with available virologic data. Interpretation: Jail health systems can reach large numbers of HCV-infected individuals. The high burden of HCV argues for universal screening in jail settings. Length of stay was strongly associated with being seen by an HCV clinician in jail. Treatment is feasible among those with longer lengths of stay. Funding: None.